Pengaruh Jenis Asam Mineral Pada Sintesis Acid Activated Montmorillonite Terhadap Struktur, Morfologi, dan Performa Bleaching Earth - Hanifah Sriamelia; Riri Jonuarti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Montmorillonite (MMT) is a clay mineral belonging to the smectite group, characterized by a large surface area, high cation exchange capacity, and a layered structure, making it a promising bleaching earth for palm oil refining. However, natural montmorillonite exhibits limitations, including a low number of active sites and limited porosity, thus requiring acid activation to enhance its performance. This study aims to analyze the effect of different mineral acids on the crystal structure, morphology, and bleaching performance of acid-activated montmorillonite. Activation was carried out using HCl, H₂SO₄, HNO₃, and H₃PO₄ at a concentration of 1 M for 3 hours. Characterization was conducted using X-ray diffraction (XRD) to determine crystallinity, scanning electron microscopy (SEM) to observe surface morphology, and UV–Vis spectrophotometry to evaluate bleaching performance. The XRD results revealed that sulfuric acid produced the largest crystal size (78.8 nm) with the highest degree of homogeneity. Activation with HCl resulted in a crystal size of 64.5 nm, H₃PO₄ yielded 68.3 nm, and HNO₃ produced 68.5 nm. SEM analysis showed the formation of new pores and a rougher surface texture after activation. HCl activation yielded the most favorable surface morphology. Bleaching tests demonstrated a significant reduction in color intensity and β-carotene content in palm oil.